Variables influencing survival in four generations of captive-born muskoxen - Lent, P.C.; Davis, W.J. (Rangifer, 1993)
Since 1967, four generations of muskoxen have been born in captivity in Alaska (399 live births, 18 abortions and 47 stillbirths), all derived from 20 females and 8 males captured on Nunivak Island. Analysis of juvenile survival was accomplished by dividing individuals into 7 classes (not born live, born live but not surviving 48 hours, survived 48 hours but < 1 week, survived 1 week but < 1 month, survived 1 month but < 6 months, survived 6 months but < 2 years, survived 2 years). Males were more frequent among live born calves (219:178, P=0.05), but greater numbers of females survived to 2 years (62:86, P<0.01). Birthweight (X=9.75 kg, N=155) did not differ between sexes nor did it significantly influence survival. Of 463 individuals, 131 showed some inbreeding but no coefficients of inbreeding exceeded 0.25 and most were less than 0.13. Analysis of variance (Kruskal-Wallis) showed a significant (P<0.05) difference between survival of inbred and non-inbred individuals. Chi-squared tests showed a greater proportion of non-inbred calves surviving to 2 years (P<0.05) but no significant differences in perinatal mortality. Offspring of the Nunivak Island cows survived significantly (P<.01) longer than those whose mothers were born in captivity, even when only non-inbred calves were compared.